Online driver model parameter identification using the Lyapunov approach based shared control - Oudainia, Mohamed Radjeb; Sentouh, Chouki; Nguyen, Anh-Tu; Popieul, Jean-Christophe (Frontiers in Control Engineering, 2022)
The work described in this paper proposes a new conflict minimization strategy in shared driving control for lane-keeping systems (LKS) in intelligent vehicles. This strategy takes into account a dynamic driver model, where the driver's parameters are identified online using the Lyapunov approach. The design of an adaptive shared controller is based on the dynamic parameters of the driver model which changes according to the driver and the situation encountered. Based on Lyapunov stability arguments, the overall asymptotic stability of the closed-loop control system with the adaptive driver model and the variation of the vehicle speed is proved and an LMI optimization is used to formulate the control design. The simulation results, conducted with the SHERPA dynamic car simulator under real-world driving situations, show the importance of integrating a dynamic driver model in the controller design in order to decrease the conflict between the driver and the lane-keeping system and to ensure the safety of the vehicle as well as to increase the confidence and acceptability of the driver.